The cardiac output optimisation following liver transplant (COLT) trial: a feasibility randomised controlled trial. Issue 8 (August 2020) - Martin, Daniel; Koti, Rahul; Gurusamy, Kurinchi; Longworth, Louise; Singh, Jeshika; Froghi, Farid; Soggiu, Fiammetta; Mallett, Susan; Schofield, Nick; Selves, Linda; Thorburn, Douglas; Eastgate, Christine; et al.
Abstract: Background: Perioperative goal directed fluid therapy (GDFT) has been shown to reduce postoperative complications following major surgery; this intervention has not been formally evaluated in the setting of liver transplantation. Methods: We conducted a prospective trial of GDFT following liver transplantation randomising patients with liver cirrhosis to either 12 h of GDFT using non-invasive cardiac output monitoring or standard care (SC). The primary outcome was feasibility. Secondary outcomes included survival, postoperative complications (Clavien-Dindo), quality of life (by EQ-5D-5L) and resource use. Trial specific follow up occurred at 90 and 180 days after surgery. Results: The study was feasible. Of 224 eligible patients, 122 were approached, 114 consented to participate and 60 were enrolled into the trial. The mean (SD) volume of IV crystalloid administered to the GDFT group during the 12-h study period was 3968 (2073) ml for the GDFT group and 2510 (1026) ml for the SC group. As regards secondary outcomes there was no difference in survival or overall complication rates. There was no significant difference in quality of life scores and resource use between the groups. Conclusion: A randomised study of GDFT following liver transplantation is feasible. A post-trial stakeholder meeting supported proceeding with a full multi-centre trial.